Unveilling Aucubin’s Pharmacological Landscape: A Bibliometric Study on Antioxidant and Anti-Inflammatory Activities - Amalia, Latifa; Murwanti, Retno; Hertiani, Triana (Faculty of Pharmacy, Universitas Gadjah Mada, 2025)
Aucubin is an iridoid glycoside known to have various pharmacological activities. Current research data shows that the pharmacological activities are very diverse and complex, so bibliometric analysis is used to facilitate understanding and provide references for further research directions. Publications related to the pharmacological activities of aucubin were obtained through the Web of Science Core Collection (WoSCC) database, which were then analyzed using Vosviewer 1.6.20 software. A total of 152 publications were obtained from the period 2013-2023, consisting of 142 articles and ten review articles. The articles came from 45 countries, 204 institutions, 862 authors, and 42 journals. Based on keyword analysis, the most frequently appearing pharmacological activities were